Process Simulation Modeling of the Linear Low-Density Polyethylene Catalytic Pyrolysis in a Fluidized Bed Reactor - Hafeez, Sanaa; Van Haute, Maarten; Constantinou, Achilleas; Al-Salem, Sultan M. (My University, 2023)
In this work, a comprehensive process simulation was developed to study and predict the pyrolysis of linear low-density polyethylene (LLDPE) in a fluidized bed reactor (FBR). The comprehensive simulation operated at 600 and 700 °C to investigate the pyrolytic oil and wax yields. These products were chosen as they mimic fuel range products available as a renewable fuel and energy source. The results showed that the oil yield decreased from 600 to 700 °C. This is because of an increase in the polyolefin polymer matrix’s vibration leading to an increase in temperature and absorbed thermal energy. In addition, there is a higher gas yield produced and negligible wax formation at 700 °C, which is beneficial in controlling accrued plastic waste (PW), of which polyethylene (PE) represents a vast proportion of via thermo-chemical conversion (TCC) technologies. The detailed process simulation was compared with experimental data under the same technology and operating conditions, and it was found that less than 10% discrepancy was observed between the two sets of data, suggesting a good validation between the two studies. Further studies showed that the diesel fuel lumped hydrocarbon (HC) range (C10-C19) was between 40 and 63% in the pyrolysis oil yield obtained. Moreover, the temperature profiles and fluidized bed distributor parameters were compared and investigated. The current simulation has proven that it can successfully predict the pyrolysis of LLDPE in an FBR.
Keywords: Fluid catalytic cracking; Fluidized bed furnaces; Fluidized beds; Linear low density polyethylenes; Supersaturation